Gakkel Ridge Basalt Geochemistry (H2O, CO2, Cl, F, S, Ti) ... - Michael, Peter (Interdisciplinary Earth Data Alliance (IEDA), 2011)
This dataset contain microprobe and FTIR data for H2O, CO2, Cl, F, S, Ti data for MORB from the Gakkel Ridge. ...